The hydroculture of calla - Lévai, P.; Turi-Farkas, Zs. (International Journal of Horticultural Science, 2001)
Hydroculture was established in the early 40’s. This technology became wide-spread in 60’s. Because of economic considerations it played little role in Hungarian ornamental plant growing. The forthcoming joining of the EEC as well as the strict enviroment protection regulations, this technology is likely to spread in our country and like in most of the West European countries, cut flowers will be grown in hydroculture. Closed systems match the most strict environmental regulations. Calla can be well adopted to this technology because of its origin and water demand. We have studied three growing methods: PUR-agrofoam, container and soil-heated, of which soil-heated proved to be the best significantly.